State Institution ‘Institute of Nephrology of the National Academy of Medical Sciences of Ukraine’: 20 years afterward - Kolesnyk, M.; Driianska, V.; Liksunova, L.; Stepanova, N.; Dudar, I.; Bagdasarova, I.; Korol, L.; Velychko, M.; Nepomnyashchy, V.; Kozliuk, N. (Ukrainian Journal of Nephrology and Dialysis, 2021)
Abstract. The Institute of Nephrology of the Academy of Medical Sciences of Ukraine was established in 2001. Since then, the Institute has been constantly evolving and, currently, it is a national scientific, methodological and medical center in the field of nephrology. The achievements of the Institute’s staff are recognized in Ukraine and the world scientific community. The article presents an analysis of the results of the Institute’s activities for 2001-2021.